Federations of female contemplative monasteries in the Latin Church in the light of the current Canon Law - Kiwior, Wiesław (Prawo Kanoniczne, 2024)
The purpose of the article is to present the subject matter of federations of female contemplative monasteries of the Latin Church in the light of the new provisions of the Canon Law, issued between 2016 and 2019, i.e. the Apostolic Constitution Vultum Dei quaerere (29th Jun 2016) with its associated implementing instruction Cor orans on female contemplative life (1st Apr 2018) and the instruction The Art of Seeking the Face of God on the formation of nuns (15th Aug 2019). After explaining the concept and nature of a federation of nuns’ monasteries (1), the author outlined the objectives of the federation (2); emphasised the mandatory membership of female contemplative monasteries in the federation (3); suggested the optimal number of monasteries forming a federation (4); drew attention to the own law of the federation, i.e. its statutes, which may be supplemented and modified in accordance with the development of the federation and its circumstances, subject to the consent of the Holy See (5); presented the individual structures of the federation and their tasks and powers, namely the collegial structures (federal assembly and federal council) (6.1.), personal structures (president, treasurer, secretary, formator and ecclesiastical assistant) (6.2.), auxiliary structures (the seat of the federation and its archives, the seat of the common initial formation – novitiate and juniorate, the financial fund and ad hoc commission) (6.3). The author also drew attention to some matters of particular importance to the Holy See, such as the compulsory and specialised formation of major superiors of all monasteries, of formators and their co-workers, and treasurers; solid initial and ongoing formation; development of an own Ratio Formationis; transfer of nuns, for various reasons, to another monastery within the federation; proper management of the temporal goods of the monasteries and federations.